2020
DOI: 10.1002/cche.10313
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of gluten‐free products in Moroccan supermarkets and e‐commerce platforms

Abstract: Background and objectives Gluten found in wheat, barley, and rye causes celiac disease. The treatment of this disease is based on the gluten‐free diet. This diet involves the consumption of gluten‐free foods including gluten‐free products (GFPs) developed by manufacturers. The objective of this survey is to estimate the nutritional composition of the gluten‐free products by comparing them to equivalent regular products (RPs) containing gluten. Findings While the fiber contents were higher in the gluten‐free pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…These elements are necessary to reward the deficits noticed in celiac patients due to malabsorption secondary to the destruction of intestinal villi. This is confirmed by a study carried out in Morocco in 2020 which showed that the nutritional quality of PFG is unbalanced [24]. This impacts on the quality of life of Moroccan patients, which is poor in Moroccan children [25].…”
Section: Fig 1 Prevalence Of Adherence To the Gluten-free Diet Table 1 Presents The Impact Of The Origin Of Residence Of Celiac Children mentioning
confidence: 64%
“…These elements are necessary to reward the deficits noticed in celiac patients due to malabsorption secondary to the destruction of intestinal villi. This is confirmed by a study carried out in Morocco in 2020 which showed that the nutritional quality of PFG is unbalanced [24]. This impacts on the quality of life of Moroccan patients, which is poor in Moroccan children [25].…”
Section: Fig 1 Prevalence Of Adherence To the Gluten-free Diet Table 1 Presents The Impact Of The Origin Of Residence Of Celiac Children mentioning
confidence: 64%
“…First, a search performed did to identify websites of supermarkets and online stores selling products through the Google search engine (www.google.com), configured to display results from Brazil in the Portuguese language. The terms used in this search were: "gluten-free products", "supermarkets gluten-free products", "website for online sale of gluten-free products", "purchase of gluten-free products", "online supermarket", "breads for sale online" and "Breads price nutritional information", according to adapted methodology proposed by Guennouni et al, (2020a).…”
Section: Methodsmentioning
confidence: 99%
“…The products were categorize into four product groups depending on the presence of gluten: baking mix (cake mix, bread mix, pie mix, puree mix and dessert mix), bread and bakery products (bread in all its forms, toast and panettone), pasta and cereal products (pasta in various forms, lasagna pasta, breakfast cereals) and cookies and cakes (cookies, filled or not, and cakes in various formats and ready for consumption). According to methodology proposed by Guennouni et al, (2020a), and the minimum number of 10 products for category did applied.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations